Inter-disciplinary European guidelines on surgery of severe obesity - Fried, M; Hainer, V; Basdevant, A; Buchwald, H; Deitel, M; Finer, N; Greve, J W M; Horber, F; Mathus-Vliegen, E; Scopinaro, N; Steffen, R; Tsigos, C; et al. (International journal of obesity (2005), 2007)
In 2005, for the first time in European history, an extraordinary Expert panel named 'The BSCG' (Bariatric Scientific Collaborative Group), was appointed through joint effort of the major European Scientific Societies which are active in the field of obesity management. Societies that constituted this panel were: IFSO - International Federation for the Surgery of Obesity, IFSO-EC - International Federation for the Surgery of Obesity - European Chapter, EASO - European Association for Study of Obesity, ECOG - European Childhood Obesity Group, together with the IOTF (International Obesity Task Force) which was represented during the completion process by its representative. The BSCG was composed not only of the top officers representing the respective Scientific Societies (four acting presidents, two past presidents, one honorary president, two executive directors), but was balanced with the presence of many other key opinion leaders in the field of obesity. The BSCG composition allowed the coverage of key disciplines in comprehensive obesity management, as well as reflecting European geographical and ethnic diversity. This joint BSCG expert panel convened several meetings which were entirely focused on guidelines creation, during the past two years. There was a specific effort to develop clinical guidelines, which will reflect current knowledge, expertise and evidence based data on morbid obesity treatment.
Keywords: intestinální absorpce; dospělí; Europe; Intestinal Absorption; dítě; Age Factors; Bariatric Surgery; Adult; týmová péče o pacienty; Adolescent; kontraindikace; Obesity; věkové faktory; lidé; Evropa; Treatment Failure; International Cooperation; Contraindications; obezita; Patient Care Team; neúspěšná terapie; bariatrická chirurgie; index tělesné hmotnosti; předoperační péče; Preoperative Care; lidé středního věku; Child; mezinárodní spolupráce; Body Mass Index; Middle Aged; mladiství; Humans